2022
DOI: 10.36660/abc.20210463
|View full text |Cite
|
Sign up to set email alerts
|

Aumento de Captação Cardíaca de 18F-FDG Induzida por Quimioterapia em Pacientes com Linfoma: Um Marcador Precoce de Cardiotoxicidade?

Abstract: Fundamento: Ainda não está estabelecido se a captação de fluorodesoxiglicose no miocárdio ocorre exclusivamente por características fisiológicas ou se representa um desarranjo metabólico causado pela quimioterapia. Objetivo: Investigar os efeitos da quimioterapia no coração dos pacientes com linfoma por tomografia por emissão de pósitrons associada a tomografia computadorizada (PET/CT) com 2-[18F]-fluoro-2-desoxi-D-glicose ( 18 F-FDG PET/CT) antes, durante e/ou após a quimioterapia. Métodos: Setenta pacientes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Dourado et al 8 observed a significant increase in myocardial 18 F-FDG uptake in patients undergoing chemotherapy for lymphoma. In more than half of patients, a percentage increase greater than 30% of left ventricular maximal SUV occurred after chemotherapy as compared with before chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dourado et al 8 observed a significant increase in myocardial 18 F-FDG uptake in patients undergoing chemotherapy for lymphoma. In more than half of patients, a percentage increase greater than 30% of left ventricular maximal SUV occurred after chemotherapy as compared with before chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Dourado et al 8 observaram elevação significativa da captação miocárdica de 18 F-FDG nos pacientes submetidos à QT por linfoma. Em mais da metade dos pacientes, o SUV máximo no miocárdio ventricular esquerdo aumentou mais de 30% pós-QT, comparando-se com o exame pré-QT.…”
Section: Discussionunclassified
“…In 2022 Dourado et al, demonstrated increased 18 F-FDG cardiac uptake after chemotherapy and interpreted the findings as a sign of cardiotoxicity (Figure in [116]).…”
Section: Nuclear Medicine Diagnostic Imaging Of Cardiotoxicity Using ...mentioning
confidence: 99%